Kakovost bibliografskih zapisov v COBIB in uporaba katalogizacijskih priročnikov - Pesjak, Damijan (Knjižnica, 2010)
The use of cataloguing manuals is one of the key factors influencing the quality of bibliographic records. The purpose of this study is to determine the quality of a random sample of bibliographic records in the Slovenian union bibliographic/catalogue database (COBIB) as well as the level of use of cataloguing manuals. The first question was checked by an analysis of 1st, 2nd and 5th area in a sample of 90 bibliographic records created in the years 2004 and 2010. To answer the second question, 126 cataloguers responded to the on-line questionnaire asking about the use of cataloguing manuals and about the quality of bibliographic records. Results showed that the quality of bibliographic records was poor and the use of cataloguing manuals was not very heavy. The problem may be solved by redesigning the existing cataloguing manuals to "how to do it" manuals solving practical problems met by cataloguers.
Keywords: katalogizacija; priročniki; bibliografski zapisi; COBIB; raziskave